Pengaruh Parameter Pemesinan CNC Bubut Terhadap MRR dan Kekasaran Permukaan Material ST 37 Menggunakan Metode Taguchi - Nova Rifqhi Syahputra; Yudi Oktriadi; Yuli Dharta (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The machining process in the manufacturing world greatly influences its quality and productivity. One of the tools in the machining process is a CNC lathe that has parameters for its use process. The process parameters in the CNC machining process are spindle speed, feed rate, and cutting depth. Some aspects that are greatly influenced by process parameters are surface roughness and MRR (Material Removal Rate), which function as efficiency in improving product quality. This study aims to analyse the effect of machining process parameters on surface roughness and MRR on test specimens made of ST 37 material. The method in this study uses the Taguchi method with the aim of increasing productivity and product and process quality. The results of this study show surface roughness based on the use of two types of tools on ST 37 material, with the DNMG 105608-MA tool producing a roughness value of 1.128 µm and the CNMG tool producing a value of 0.865 µm. Meanwhile, the MRR value produced by the DNMG 105608-MA tool is 1,072.8 mm³/s, which is slightly superior to that of the CNMG 120408-MK tool, with an MRR value of 1,032.5 mm³/s.